Soil-pile-structure interaction effects on high-rise building under seismic shaking - Thapa, Umesh Jung; Karki, Ramesh (Journal of Innovations in Engineering Education, 2019)
In this paper, study of the response (base shear, time period, storey drift, storey displacement) of a structure is done for the tall building including basement with fixed base and with pile foundation considering Soil Structure Interaction (SSI). Finite element based program ETABS2016 v16.1.0 is used for the analysis of the superstructure. Seismic analysis is done to get the dynamic response of superstructure for two types of model,one model is with fixed baseand second is Model with Winkler spring for Chhaya Center, Thamel, a high rise building with 14 story including double basements. Itisobserved with the consideration of Soil Structure Interaction (SSI). The soil is replaced by spring and assigned at joints. El Centro earthquake (1940) is used for time history analysis. The response obtained due to SSI effect is compared with fixed based model. Results of analysis presented include the comparison of natural periods, base shears, displacements and overturning moment. It is observed that the natural periods increase and the base shears decrease as the base become more flexible.